Phylogeography, phylogenetics and evolution of the redfins (Teleostei, Cyprinidae, Pseudobarbus) in southern Africa - Bloomer, Paulette (University of Pretoria, 2013)
Thesis (PhD (Genetics))--University of Pretoria, 2007.